A tissue preparation to characterize uterine fibroid tissue properties for thermal therapies. Issue 8 (25th June 2019) - Dillon, Christopher; Rezvani, Maryam; McLean, Hailey; Adelman, Marisa; Dassel, Mark; Jarboe, Elke; Janát‐Amsbury, Margit; Payne, Allison
Abstract : Purpose: Treating uterine fibroids with less invasive therapies such as magnetic resonance‐guided focused ultrasound (MRgFUS) is an attractive alternative to surgery. Treatment planning can improve MRgFUS procedures and reduce treatment times, but the tissue properties that currently inform treatment planning tools are not adequate. This study aims to develop an ex vivo uterine fibroid model that can emulate the in vivo environment allowing for characterization of the uterus and fibroid MR, acoustic, and thermal tissue properties while maintaining viability for the necessary postsurgical histopathological assessments. Methods: Women undergoing a hysterectomy due to fibroid‐related symptoms were invited to undergo a preoperative pelvic MRI and to permit postoperative testing of their uterine specimen. Patients that declined or could not be scheduled for a pre‐operative MRI were still able to allow post‐operative testing of their excised tissue. Following surgical removal of the uterus, nonmorcellated tissues were reperfused with a Krebs‐Henseleit buffer solution. An MR‐compatible perfusion system was designed to maintain tissue viability inside the MR suite during scanning. MR imaging protocols utilized preoperatively were repeated on whole sample, reperfused ex vivo uterus specimens. Thermal properties including thermal diffusivity and thermal conductivity of the uterus and fibroids were determined using an invasive needle sensor device in 50% of the specimens. Acoustic property measurements (density, speed of sound and attenuation) were obtained for approximately 20% of the tissue samples using both through‐transmission and radiation force balance techniques. Differences between fibroid and uterus and in vivo and ex vivo measurements were evaluated with a two‐tailed Student t test. Results: Fourteen patients participated in the study and measurements were obtained from 22 unique fibroids. Of the 16 fibroids available for preoperative MRI testing, 69% demonstrated classic hypo‐intensity relative to the myometrium, with the remainder presenting with iso‐ (25%) or hyper‐intensity (6%). While thermal diffusivity was not significantly different between fibroid and myometrium tissues (0.217 ± 0.047 and 0.204 ± 0.039 mm 2 /s, respectively), the acoustic attenuation in fibroid tissue was significantly higher than myometrium (0.092 ± 0.021 and 0.052 ± 0.023 Np/cm/MHz, respectively). When comparing in vivo with ex vivo MRI T1 and T2 measurements in fibroids and myometrium tissue, the only difference was found in the fibroid T2 property ( P  < 0.05). Finally, the developed perfusion protocol successfully maintained tissue viability in ex vivo tissues as evaluated through histological analysis. Conclusions: This study developed an MR‐compatible extracorporeal perfusion technique that effectively maintains tissue viability, allowing for the direct measurement of patient‐specific MR, thermal, and acoustic property values for both fibroid and myometrium tissues. These measured tissue property values will enable further development and validation of treatment planning models that can be utilized during MRgFUS uterine fibroid treatments.